2019
DOI: 10.1002/oby.22535
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Consistency in Timing of Exercise Performance and Exercise Levels Among Successful Weight Loss Maintainers

Abstract: Objective: This study aimed to evaluate whether consistency in time of day that moderate-to vigorousintensity physical activity (MVPA) is performed relates to MVPA levels among successful weight loss maintainers in the National Weight Control Registry. Methods: Participants (n = 375) reporting MVPA on ≥ 2 d/wk completed measures of temporal consistency in physical activity (PA) (> 50% of MVPA sessions per week occurring during the same time window: early/ late morning, afternoon, or evening), PA levels, PA aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…2). In a separate study, Schumacher et al [46] also found that weight loss maintainers self-reported engaging in high amounts of MVPA. In that study, participants who were classified as temporally consistent exercisers (i. e., regularly exercised at the same time of day) engaged in more MVPA (350 min/wk) compared to temporally inconsistent exercisers (285 min/wk).…”
Section: Effect Of Exercise Timing On Body Weight and Body Compositionmentioning
confidence: 92%
See 2 more Smart Citations
“…2). In a separate study, Schumacher et al [46] also found that weight loss maintainers self-reported engaging in high amounts of MVPA. In that study, participants who were classified as temporally consistent exercisers (i. e., regularly exercised at the same time of day) engaged in more MVPA (350 min/wk) compared to temporally inconsistent exercisers (285 min/wk).…”
Section: Effect Of Exercise Timing On Body Weight and Body Compositionmentioning
confidence: 92%
“…There is accumulating evidence from observational and clinical studies that the timing of exercise and PA affects body weight regulation [42][43][44][45][46][47][48][49]. Some evidence suggests that morning exercise and PA is associated with more favorable changes in weight and body composition [42,45] and increased ability to prevent weight regain [46,47,49]. However, some data suggest that evening exercise may be more beneficial for reducing fat [44,48] (▶table 1).…”
Section: Effect Of Exercise Timing On Body Weight and Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both attenuated weight loss and weight loss variability have been attributed to compensatory mechanisms such as reductions in other components of EE and/or increases in energy intake (EI) [1,[6][7][8][9][10][11][12]. The timing (i.e., time of day) of exercise Nutrients 2022, 14, 816 2 of 13 may affect these compensatory responses and the weight loss response [13][14][15][16][17][18][19][20][21][22][23]. In addition, exercise timing may influence factors related to overall adherence and engagement in exercise, thereby influencing body weight [24].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest exercising at the same time each day (i.e., "time-structured") versus different times of the day (i.e., "sporadic") is important for long-term exercise adherence [10,11]. Therefore, investigating the efficacy of exercising at different times of day is essential.…”
Section: Introductionmentioning
confidence: 99%